Efficacy and safety of AnluoHuaxian pills on chronic hepatitis B with normal or minimally elevated alanine transaminase and early liver fibrosis: A randomized controlled trial. (15th July 2022) - Xiao, Huan-Ming; Shi, Mei-Jie; Jiang, Jun-Min; Cai, Gao-Shu; Xie, Yu-Bao; Tian, Guang-Jun; Xue, Jing-Dong; Mao, De-Wen; Li, Qin; Yang, Hong-Zhi; Guo, Hui; Lei, Chun-Liang; et al.
Abstract: Ethnopharmacological relevance: The AnluoHuaxian pill (AHP) is a widely used patented medicine for chronic hepatitis B (CHB) patients with advanced fibrosis or cirrhosis that has been used in China for more than 15 years. However, data are lacking on whether monotherapy with AHP can be effective in CHB patients with alanine aminotransferase (ALT) levels less than 2 times the upper limit of normal (ALT<2ULN) and early liver fibrosis (F ≤ 2). Aim of the study: We aimed to investigate whether monotherapy with AHP improves liver histology in these patients. Materials and methods: In this double-blind, randomized, placebo-controlled trial, 270 CHB patients with ALT<2ULN and F ≤ 2 were treated in 12 hospitals in China. The patients were randomly assigned to an intervention (AHP) group and a placebo group at a ratio of 2:1. Of these 270 enrolled patients, 147 had paired liver biopsies. The primary end point was histological change after 48 weeks of treatment. Results: Per-protocol analysis revealed that the rate of histologic improvement in liver fibrosis patients in the AHP group was significantly higher than that in the placebo group (37.7% vs. 19.5%, P  = 0.035) after 48 weeks of treatment, which was consistent with results from intention-to-treat and sensitivity analyses. Moreover, after adjusting for baseline characteristics, AHP was superior to placebo with respect to improving liver fibrosis (odds ratio [OR] = 2.58, 95% confidence interval [CI]: (1.01, 6.63), P  = 0.049) and liver histology (OR = 3.62, 95% CI: (1.42, 9.20), P  = 0.007). In noninvasive measurement of liver fibrosis (FibroScan®), the level of liver stiffness measurement (LSM) had decreased significantly at 48 weeks (5.1 kPa) compared with that at baseline (5.7 kPa) ( P  = 0.008) in the AHP group, whereas it did not decrease significantly in the placebo group. Cirrhosis developed in one patient in the placebo group but in no patients in the AHP group. No serious side effects occurred in the AHP-treated patients. Conclusions: Treatment of CHB patients who had ALT<2ULN and F ≤ 2 with the traditional Chinese medicine AHP for 48 weeks improves liver fibrosis. However, due to the short duration of treatment and the limited sample size of liver pathology, the long-term benefits of AHP in reducing fibrosis and the risk of cirrhosis and hepatocellular carcinoma in these patients need to be further studied in the future. Graphical abstract: Image 1 Highlights: Increasing experts agree that CHB patients with ALT<2ULN are deserved treatment to prevent progression of fibrosis. But the anti-fibrosis efficacy of antiviral therapy is limited in these patients. More notably, no treatment in recent guidelines is available for patients with ALT<2ULN and G1F1. Treatment of CHB patients with ALT<2ULN and F≤2 with AHP for 48 weeks is beneficial for liver fibrosis improvement.